An unusual presentation of probable dementia: Rhyming, associations, and verbal disinhibition. Issue 2 (28th February 2014) - Robinson, Gail; Ceslis, Amelia
<x xml:space="preserve">Abstract</x> We report a case of probable Alzheimer's disease who presented with the unusual feature of disinhibited rhyming. Core language skills were largely intact but generative language was characterized by semantic‐based associations, evident in tangential and associative content, and phonology‐based associations, evident in rhyming, in the context of prominent executive dysfunction. We suggest this pattern is underpinned by a failure to terminate or inhibit verbal associations resulting in a 'loosening' of associations at the level of conceptual preparation for spoken language.